Prevalence, assessment, and antimicrobial resistance patterns of Salmonella from raw chicken eggs in Haramaya, Ethiopia - Jelalu Kemal; Berhanu Sibhat; Sissay Menkir; Desta Beyene (Journal of Infection in Developing Countries)
Introduction: The presence of antimicrobial-resistant Salmonella in poultry and poultry products, including eggs, is a global public health concern. This study aimed to estimate the levels and patterns of antimicrobial resistance of Salmonella from chicken eggs and assess consumers’ raw egg consumption and farmers’ handling practices. Methodology: A total of 300 egg samples were collected from Haramaya open market (n = 150) and Haramaya University poultry farm (n = 150) in Ethiopia. Questionnaires were administered to egg sellers and buyers. A sterile cotton swab was used to sample the surface of eggs. The shells were sterilized and the egg content sampled. Isolation was done using the conventional methods for the detection of Salmonella, following the standard guidelines from ISO 6579. Sensitivity to 12 selected antibiotics was tested following the procedure of the Clinical and Laboratory Standards Institute. Results: A level of 5.3% was observed among eggs shells from the open market and 0% among egg shells from the poultry farm, for an overall level of 2.7%. There was a significant difference (p = 0.004) between the prevalence of Salmonella spp. in sample site and sample type. Of the antimicrobials tested, Salmonella isolates were all resistant to erythromycin and clindamycin. Isolates were sensitive to ciprofloxacin (100%) and chloramphenicol (87.5%). All isolates were resistant to multiple antibiotics. One-third of the consumers were found to have eaten raw eggs for perceived medicinal values. Conclusion: To minimize the potential contamination of eggs by pathogens, the eggs should be properly handled, transported, and stored.